Interspecific divergence of circadian properties in duckweed plants. (8th March 2022) - Isoda, Minako; Ito, Shogo; Oyama, Tokitaka
Abstract: The circadian clock system is widely conserved in plants; however, divergence in circadian rhythm properties is poorly understood. We conducted a comparative analysis of the circadian properties of closely related duckweed species. Using a particle bombardment method, a circadian bioluminescent reporter was introduced into duckweed plants. We measured bioluminescence circadian rhythms of eight species of the genus Lemna and seven species of the genus Wolffiella at various temperatures (20, 25, and 30°C) and light conditions (constant light or constant dark). Wolffiella species inhabit relatively warm areas and lack some tissues/organs found in Lemna species. Lemna species tended to show robust bioluminescence circadian rhythms under all conditions, while Wolffiella species showed lower rhythm stability, especially at higher temperatures. For Lemna, two species ( L. valdiviana and L. minuta ) forming a clade showed relatively lower circadian stability. For Wolffiella, two species ( W. hyalina and W. repanda ) forming a clade showed extremely long period lengths. These analyses reveal that the circadian properties of species primarily reflect their phylogenetic positions. The relationships between geographical and morphological factors and circadian properties are also suggested. SUMMARY STATEMENT: This study addresses questions about the relationships between the circadian rhythm properties of duckweed species and their phylogenetic positions. Our findings on the phylogenetic restriction of circadian properties in plants are important for understanding the diversity of circadian systems among strains/species.